Fiscal policy must be promoted from colombian economic policy? - Pinilla Perez, Patricia; Niño Lievano , Fabio Augusto; Suárez Suárez , David Andres; Gutierrez Espalza, Alejandra Maria (Universidad Francisco de Paula Santander, 2016)
Result of applying fiscal policy to the economic policyin Colombia, points out that tax reforms, in principle, are not stated in the proposals of the elected presidential candidates, but to the extent that the National Development Plan can be implemented, it is necessary to resort to seeking new income and these are effectively ensured, faster through tax reforms, applied as fiscal policy measures.The initial effects of the tax reform at lDec2016, compared to tax benefits for companies that support science and technology and not for those generating new jobs and growth in the economy, especially those in sectors of the Colombian economy, more affected by violence, armed conflict and climatic phenomena, with the aim of stimulating economic growth and its effects would soon be noticed in productive, extractive and transformation sectorIt is evident that fiscal policy must be generated from the postulates of economic policy, which are discussed in the topics to be discussed in the development plan proposed by the president of shift of Colombia. This will meet the management indicators of the president of the republic in the field of economic development